Model dan Strategi Pengembangan Bisnis Pondok Pesantren Modern Subulussalam Padang Pariaman - Harahap, Solehuddin; Syarif, Dafiar (Universitas Islam Raden Rahmat, 2022)
This research departs from the many Islamic boarding schools that have transformed by incorporating socio-economic functions into the activity program of Islamic boarding schools, one of the Islamic boarding schools that is trying to be independent in economic activities and conducting local businesses is Pondok Pesantren Modern Subulussalam located in the Panyalai village of Nagari Lubuk Pandan, District 2x11 Six neighborhoods, Kabupaten Padang Pariaman. This study uses qualitative research by looking at the business strategy used and then analyzing it with a SWOT analysis. The results of the strategic research implemented by Pondok Pesantren Modern Subulussalam Foundation include collaborating with various Islamic financial institutions, establishing partnerships with the government and related institutions, building micro-enterprises that can be marketed, developing Kopontren human resources to continue to face challenges, and conducting training. entrepreneurship in Islamic boarding schools.